The principal's strategy in improving quality differentiated instruction through academic supervision at SDN Sumur Welut 3/440 Surabaya - Vira Nur Umaimah; Syunu Trihantoyo (Edu Learning : Journal of Education and Learning, 2023)
Kurikulum merdeka dilaksanakan untuk membangkitkan motivasi dan hasil belajar yang berfokus pada siswa. Dengan ini kesuksesan implementasi kurikulum merdeka memang dapat dikatakan lebih optimal, namun masih terdapat gap yakni (1) rendahnya motivasi belajar siswa, (2) adanya learning loos, keadaan yang mengakibatkan siswa mengalami kemunduran dalam hal prestasi belajar, (3) implementasi pembelajaran berdiferensiasi juga memberikan tantangan bagi guru/pendidik dalam mengimplementasikannya. Kepala sekolah diberikan wewenang dalam melakukan perencanaan, pengorganisasian, pelaksanaan dan pengendalian di lembaga sekolah. Dengan ini melalui strategi yang diambil oleh kepala sekolah sebagai seorang kepala sekolah di lembaga pendidikan, sebisa mungkin dapat memberikan dampak keberhasilan yang maksimal.Tujuan dari penelitian ini adalah untuk mengkaji secara mendalam terkait strategi strategi kepala sekolah melaksanakan supervisi akademik pada pembelajaran berdiferensiasi, mengkaji secara mendalam terkait strategi kepala sekolah dalam meningkatkan kualitas pembelajaran berdiferensiasi, dan mengkaji secara mendalam terkait dampak dari strategi kepala sekolah dalam peningkatan kualitas pembelajaran berdiferensiasi di SDN Sumur Welut 3/440 Surabaya. Dalam rangka mencapai tujuan penelitian tersebut peneliti menggunakan metode kualitatif dengan pendekatan fenomenologi. Teknik pengumpulan data yang peneliti gunakan yaitu observasi, wawancara, dan dokumentasi dengan informan yakni kepala sekolah, guru kelas 1, dan guru kelas 4. Teknik analisis data yang peneliti gunakan adalah teknik analisis data milik Miles dan Huberman yang terdiri dari empat tahapan, yaitu Kondensasi, pengumpulan data, penyajian data, dan penarikan kesimpulan. Kesimpulan dari penelitian ini, yaitu (1) Strategi kepala sekolah melaksanakan supervisi akademik perencanaan kepala sekolah membuat program supervisi berupa sosialisasi, setelah itu penyusunan dan pengkonfirmasian perangkat pembelajaran. Pelaksanaan disesuaikan dengan perangkat pembelajaran yang telah disusun di tahap perencanaan selanjutnya pengamatan pelaksanaan pembelajaran guru dan penilaian sesuai instrumen observasi. Evaluasi pemberian pertanyaan evaluasi kepada guru setelah pembelajaran dan tindak lanjut diberikan berupa pelaksanaan forum rapat mengenai evaluasi supervisi akademik, atau diklat dan workshop menyesuaikan kebutuhan. (2) Strategi kepala sekolah dalam meningkatkan kualitas pembelajaran berdiferensiasi, diferensiasi konten kepala sekolah menganalisis kesiapan siswa, guru, konten materi pembelajaran berupa (RPP/Modul ajar) disesuaikan dengan tujuan pembelajaran dan CP (capaian pembelajaran). Tahap diferensiasi proses guru harus menguasai dan memahami betul mengenai konten materi yang akan diberikan kepada siswanya. Tahap diferensiasi produk kepala sekolah melakukan pengembangan pada produk hasil karya siswa sebisa mungkin sekolah akan memfasilitasi agar proyek siswa bisa terlaksana sebagaimana mestinya. (3) Dampak dari strategi kepala sekolah dalam peningkatan kualitas pembelajaran berdiferensiasi, dampak positif (keberhasilan) siswa siswa merasa senang dengan pembelajaran di kelas karena mampu memahami materi serta hasil belajar/asesmen siswa baik, dampak negatif (kekurangan/kegagalan), guru masih mendapatkan tantangan dalam melayani pembelajaran dan pada siswa yang masih belum memahami mengenai materi pembelajaran guru mengupayakan tindak lanjut berupa pembimbingan secara intens kepada siswa tersebut. Kata kunci : Dampak Strategi Kepala Sekolah, Pembelajaran Berdiferensiasi, Strategi Kepala Sekolah, Supervisi Akademik. The independent curriculum is implemented to generate motivation and learning outcomes that focus on students. With this the success of the implementation of the independent curriculum can indeed be said to be more optimal, but there are still gaps, namely (1) low student learning motivation, (2) there is learning loss, a situation that causes students to experience setbacks in terms of learning achievement, (3) the implementation of differentiated learning is also provide challenges for teachers / educators in implementing it. The school principal is given authority in planning, organizing, implementing and controlling in school institutions. With this, through the strategy taken by the principal as a principal in an educational institution, as much as possible to have the maximum impact on success.The purpose of this study is to examine in depth the strategies of school principals carrying out academic supervision on differentiated learning, examine in depth the strategies of school principals in improving the quality of differentiated learning, and examine in depth the impact of school principals' strategies in improving the quality of differentiated learning in SDN Sumur Welut 3/440 Surabaya. In order to achieve the research objectives, researchers used qualitative methods with a phenomenological approach. The data collection techniques that the researchers used were observation, interviews, and documentation with informants namely school principals, grade 1 teachers, and grade 4 teachers. The data analysis technique that researchers used was Miles and Huberman's data analysis technique which consisted of four stages, namely Condensation , data collection, data presentation, and drawing conclusions.The conclusions from this research are (1) the principal's strategy for carrying out academic supervision planning for the principal is to create a supervision program in the form of outreach, after which preparation and confirmation of learning tools. The implementation is adjusted to the learning tools that have been prepared in the planning stage, then the observation of the implementation of teacher learning and assessment according to the observation instrument. Evaluation of giving evaluation questions to teachers after learning and follow-up is given in the form of implementing meeting forums regarding evaluation of academic supervision, or training and workshops according to needs. (2) The school principal's strategy in improving the quality of learning is differentiated, the principal's content differentiation analyzes the readiness of students and teachers, the content of learning materials in the form of (RPP/teaching modules) is adjusted to the learning objectives and CP (learning achievements). In the differentiation stage of the process, the teacher must really master and understand the content of the material that will be given to his students. The product differentiation stage of the school principal develops products made by students as much as possible so that the school will facilitate student projects so that they can be carried out as they should. (3) The impact of the principal's strategy on improving the quality of learning is differentiated, the positive impact (success) on students is that students feel happy with learning in class because they are able to understand the material and the learning outcomes/student assessments are good, negative impacts (lack/failure), teachers still face challenges in serving learning and for students who still do not understand about the learning material the teacher seeks follow-up in the form of intense guidance to these students. Keywords: Principal's Strategy, Differentiated Instruction, Academic Supervision, Impact of Principal's Strategy